Review for the book: Shokhin S.O., Kudryashova E.V. The legal framework for strategic planning in contemporary Russia, Monograph. Moscow, MGIMO University Publ, 2022. 126 p. ISBN 978-5-9228-2622-8 (print). - V. V. Grib; A. Cenerelli (Правоприменение, 2024)
In 2022 the MGIMO University Publishing house has released the monograph authored by Shokhin and E.V. Kudryashova “The Legal Framework for strategic planning in contemporary Russia”. This review represents the book for the international audience. There is also a discussion of the monograph’s key points.